Best $m$-term approximation of the classes $B ^{r}_{∞, θ}$ of functions of many variables by polynomials in the haar system - Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We obtain the exact-order estimate for the best $m$-term approximation of the classes $B ^{r}_{∞, θ}$ of periodic functions of many variables by polynomials with respect to the Haar system in the metric of the space $L_q,\quad 1 < q < ∞$.